2019
DOI: 10.1016/j.neurobiolaging.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Older adults fail to form stable task representations during model-based reversal inference

Abstract: Older adults struggle in dealing with changeable and uncertain environments across several cognitive domains. This has been attributed to difficulties in forming adequate task representations that help navigate uncertain environments. Here, we investigate how, in older adults, inadequate task representations impact on model-based reversal learning. We combined computational modeling and pupillometry during a novel model-based reversal learning task, which allowed us to isolate the relevance of task representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
43
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 37 publications
14
43
0
Order By: Relevance
“…Interestingly, these results are in accord with previous studies in the non-social domain and extend them to social inference. Our finding of older adults' stronger prior beliefs about volatility is consistent with very recent findings of age-related differences in learning in uncertain environments (Hämmerer et al, 2018). In this study, OA were similarly found to overestimate reversal probabilities (and thus volatility) in a reversal learning paradigm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, these results are in accord with previous studies in the non-social domain and extend them to social inference. Our finding of older adults' stronger prior beliefs about volatility is consistent with very recent findings of age-related differences in learning in uncertain environments (Hämmerer et al, 2018). In this study, OA were similarly found to overestimate reversal probabilities (and thus volatility) in a reversal learning paradigm.…”
Section: Discussionsupporting
confidence: 92%
“…Such social skills might even become more essential the more we rely on the support of others in older age. However, there is reason to hypothesize that social inference in dynamic social contexts changes over the course of the lifespan: Evidence from studies investigating learning in non-social environments indicates that older adults compute and represent uncertainty in changing environments differently than younger adults (Hämmerer et al, 2018;Nassar et al, 2016). It is well conceivable that these age-related differences play an important role also when older adults navigate social environments, especially in light of evidence showing compromised socio-cognitive skills in human aging (Henry, Phillips, Ruffman, & Bailey, 2013;Reiter, Kanske, Eppinger, & Li, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Across different task domains, performance limitations in children and older adults are often either due to preservation or an increased impact of environmental information on behavior (Alarcón and Bonardi, 2020;Carroll et al, 2007;Cepeda and Munakata, 2007;Chatham et al, 2009;Craik and Bialystok, 2006;Crone et al, 2004a,b;De Boer et al, 2017;Gonthier et al, 2019;Head et al, 2009;Lindenberger and Mayr, 2014;Mayr et al, 2015;Munakata et al, 2012;Ridderinkhof et al, 2002;Rutledge et al, 2009;Troller-Renfree et al, 2020). Previous work has identified lifespan differences in learning (Eppinger et al, 2008(Eppinger et al, , 2009(Eppinger et al, , 2013Chowdhury et al, 2013;Crone and Van der Molen, 2004;Hämmerer et al, 2011;Rutledge et al, 2009;Samanez-Larkin et al, 2010, 2014Van den Bos et al, 2012;Van Der Schaaf et al, 2011) and suggested that they might relate to normative impairments in belief updating (De Boer et al, 2017;Hämmerer et al, 2019;. However, it is currently unclear how computational differences across age groups are linked to performance limitations and, particularly, to the seemingly contradictory tendencies to either perseverate on previous behavior or to rely more strongly on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…These findings demonstrate the possibility of boosting model-based control in older adults. Indeed, normative aging is associated with modelbased learning deficits such as a failure to maintain stable task representations (Hämmerer et al, 2018) and a diminished capacity to integrate uncertainty into decision-making (Eppinger et al, 2013;Nassar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%